Analisis Prediksi Kondisi Kekerasan Jalan Raya menggunakan Aplikasi IRI untuk Penanganan Jalan (Studi Kasus: Ruas Jalan Nasional Kota Jalan Nasional Kota Ruas, Gresik-Sadang) - Kogoya, Desmin; Nugroho, Laksono Djoko; Oetomo, Wateno (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2024)
Road pavement conditions will overcome the decline in service levels over time. The decline in the level of road services is characterized by the occurrence of damage to the structure of the pavement layer of the road and left in a long period of time it will be able to renew the level of the layer of security that can increase security, comfort, and smoothness in crossing. The purpose of this study is to analyze the influence of traffic, pavement structure and CBR on the value of road IRI and estimation of road pavement conditions in the next 10 years. The data used in this research are traffic load, CBR, rainfall and road pavement structure. The analysis was carried out using a method developed by IRI (International Roughness Index) to predict road conditions. Data collection was carried out by surveying road damage using the ROADROID application and (RCI) the Road Condition Index as preliminary data. This research will be applied to data collected from the national road network in East Java province, specifically the Bts national road section. Gresik City - Sadang. To facilitate analysis, the road segment is divided into 3 segments with the length of each km segment starting from Km 20 to Km 40. The results of data analysis show an increase in traffic load of 31% will result in an increase in IRI value of 0.061 m / km per year, a structural value of 11.32% resulting in an increase in IRI of 0.034 m / km per growth, based on a CBR of 38% resulting in an increase IRI value of 0.017 m / km per year. The predicted results of road pavement conditions on Km 40, 20 and 20 sections are minor damaged roads, for Km 20, 40 routine maintenance sections.